The effects of Nordic Walking on health in adults: A systematic review - Liu, Yangjun; Xie, Wei; Ossowski, Zbigniew (Journal of Education, Health and Sport, 2022)
Objective: Nordic walking is a physical activity gaining more and more interest among adults. The aim of the study was to conduct a systematic review to determine the effects of Nordic walking on the physical and mental health of adults Method: We identified Nordic walking related randomized controlled trials (RCTs) in the electronic databases PubMed, EBSCO and CNKI, however 19 from 47 studies were selected for evaluation and systematic review based on relevant data. Results: Most of the study subjects were in the middle-aged and elderly clinical population, and three studies included non-clinical populations. The intervention was conducted most often three times a week for 8 weeks or more. The main effects of Nordic Walking were physical and psychological beniphytes, in particular the improvement of circulatory and respiratory and quality of life. All studies reported at least one beneficial effect of Nordic walking compared to the control group. Conclusion: Nordic walking has some beneficial effects on the physical and mental health of adults with or without clinical symptoms.